Existence Solutions of Vector Equilibrium Problems and Fixed Point of Multivalued Mappings - Kanokwan Sitthithakerngkiet; Somyot Plubtieng (Abstract and Applied Analysis)
Let K be a nonempty compact convex subset of a topological vector space. In this paper-sufficient conditions are given for the existence of x∈K such that F(T)∩VEP(F)≠∅, where F(T) is the set of all fixed points of the multivalued mapping T and VEP(F) is the set of all solutions for vector equilibrium problem of the vector-valued mapping F. This leads us to generalize and improve some existence results in the recent references.